2021
DOI: 10.1111/papt.12363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhythmic eye movements during a virtual reality exposure paradigm for spider‐phobic patients

Abstract: Rhythmic eye movements performed during eye movement desensitization and reprocessing (EMDR) therapy have been shown to evoke a physiological de-arousal pattern. Objectives. Here, we examined whether the efficacy of a virtual reality exposure therapy (VRET) paradigm for phobic patients could be improved by adding rhythmic eye movements.Design. Spider-phobic patients (N = 53) were randomly assigned to either a group performing rhythmic eye movements or a control group undergoing exposure without such eye moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Another RCT by Kleim et al (2014) revealed that sleep following VRET led to higher reductions of arachnophobia and catastrophic fear-related cognitions compared to wakefulness after exposure. Rhythmic eye movements during VRET, on the other hand, did not increase its effectiveness, as shown by another RCT (Reitmaier et al, 2022). According to an RCT by Tardif, Therrien, and Bouchard (2019), adding tactile and haptic stimuli to a one-session VRET did also not increase its effectiveness.…”
Section: Therapy Studiesmentioning
confidence: 91%
“…Another RCT by Kleim et al (2014) revealed that sleep following VRET led to higher reductions of arachnophobia and catastrophic fear-related cognitions compared to wakefulness after exposure. Rhythmic eye movements during VRET, on the other hand, did not increase its effectiveness, as shown by another RCT (Reitmaier et al, 2022). According to an RCT by Tardif, Therrien, and Bouchard (2019), adding tactile and haptic stimuli to a one-session VRET did also not increase its effectiveness.…”
Section: Therapy Studiesmentioning
confidence: 91%
“…Fulltext articles were obtained for these abstracts, and all were independently reviewed by two authors (MTE and ER). Of the 53 articles selected for full-text review, 27 articles (Gujjar et al, 2019;Shiban et al, 2017;Shiban et al, 2015;Diemer et al, 2013;Malbos E et al, 2013;Donahue et al, 2009;Norrholm et al, 2016;Levy et al, 2016;de Quervain et al, 2011;Cote and Bouchard, 2005;Wiederhold et al, 2002;Tardif et al, 2019;Hur et al, 2021;Kaussner et al, 2020;Loucks et al, 2019;Mühlberger et al, 2001;Borghese et al, 2022;Diemer et al, 2023;Gramlich et al, 2021;Hong et al, 2017;Premkumar et al, 2021;van 't Wout-Frank et al, 2019;Wechsler et al, 2021;McGlade et al, 2023;McInerney et al, 2021;Price et al, 2015;Reitmaier et al, 2022), representing 1046 participants, were retained for final inclusion (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 3 shows that all 27 studies used biomarkers as outcome measures. Thirteen of the studies (Gujjar et al, 2019;Shiban et al, 2017;Shiban et al, 2015;Diemer et al, 2013;Malbos E et al, 2013;Donahue et al, 2009;Kaussner et al, 2020;McGlade et al, 2023;Borghese et al, 2022;Reitmaier et al, 2022;Gramlich et al, 2021;Premkumar et al, 2021;van 't Wout-Frank et al, 2019) also used biomarkers as measures of inter-session or intra-session habituation. These thirteen studies measured physiological responses at the beginning and/or during the exposure and/or at the end of each exposure session, or they measured changes in physiological responses between specific scenarios during the exposure.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Second, the movement and interaction within virtual environments were generally limited. Only four studies utilized the actual physical movement of the patient in therapy (Krijn et al, 2004;Whitney, 2005;Meyerbröker et al, 2018;Reitmaier et al, 2022) and the method for interacting was also generally outdated, with no studies utilizing body tracking. Similarly, there were only two studies utilizing haptic feedback (Meindl et al, 2019;Jiang et al, 2020) and three studies utilizing olfactory feedback (Gujjar et al, 2017;Gujjar et al, 2018Gujjar et al, , 2019.…”
Section: Gaps Between Examined Vr Setups and Contemporary Vr Technologymentioning
confidence: 99%
“…For treating certain types of specific phobia, the use of six degrees of freedom tracking allowing patients to physically approach feared objects (e.g., Reitmaier et al, 2022) may be an important feature. Further, any measures to increase comfort and reduce cybersickness would allow patients to stay in the environments for extended periods, mimicking the gold standard treatments (Öst, 2012).…”
Section: Gaps Between Examined Vr Setups and Contemporary Vr Technologymentioning
confidence: 99%